The current context of producing Trigo in Rio Grande do Sul - Camponogara, Alexandre da Silveira; Gallio, Ezequiel; Borba, Willian Fernando de; Georgin, Jordana (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
This paper presents an approach to the importance of wheat in the state of Rio Grande do Sul and shows the current position and the production of the state’s wheat cultivation, and Brazil. With the reduction of subsidies and the consolidation of MERCOSUR, the situation worsened thereafter placed himself in check the development of the wheat crop in the state and in the country. But before the existing productive capacity in some crops, if gains importance to the idea that, before funding policies, the wheatfield can still remain in the state. However, the rising costs of internal production, before a much cheaper Argentine production, has virtually eliminated the possibility of wheat production, especially among those with lower seeded area. As a result, thenational wheat relies heavily on the continuity of research that get even more varieties adapted to our climate and soil, making use of the management of seed treatment with fungicides and insecticides, aimed at increasing productivity and, consequently, the income of farmers who are willing to produce the cereal